The Pocket Psychiatrist: Tools to enhance psychiatry education in family medicine. (July 2015) - Bass, Deanna; Brandenburg, Dana; Danner, Christine
Primary care is the setting where the majority of patients seek assistance for their mental health problems. To assist family medicine residents in providing effective care to patients for mental health problems during residency and after graduation, it is essential they receive training in the assessment, diagnosis, and treatment of common mental health conditions. While there is some limited education time with a psychiatrist in our department, residents need tools and resources that provide education during their continuity clinics even when the psychiatrist is not available. Information on two tools that were developed is provided. These tools include teaching residents a brief method for conducting a psychiatric interview as well as a means to access evidence-based information on diagnosis and treatment of mental health conditions through templates available within our electronic medical record.